HELLP syndrome, associated with eclampsia, preeclampsia, in one hundred cases, the complications, maternal morbidity and mortality: the near miss and missed obstetric scenarios - Devabhaktuni, Pratibha; Ponnuru, Malathi; Vangala, Lahari R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: The investigations done, complications observed, mode of delivery, management of complications, the perinatal outcome, the maternal mortality, the lessons learnt have been outlined. The referral to higher tertiary care Institutes has been analysed. The goals of management were, control of hypertension, prevention of convulsions, assessment of the severity of HELLP syndrome, identification of associated complications and chances of fetal salvage, a decision to be made regarding the mode of delivery, keeping the blood products ready, anaesthetist and paediatrician to be informed, consultation of nephrologist, cardiologist, neurophysician, ophthalmologist, gastroenterologist, surgeon as required in the particular case and continued vigilance in the postpartum period. Methods: This is a prospective observational study of one hundred cases of HELLP syndrome managed at two tertiary care Institutes. Twenty-five cases, managed at CARE Institute of Medical sciences, during the years 2011 to 2013 and 75 cases from the Institute of Obstetrics and Gynaecology at Modern Government Maternity Hospital, MGMH, Osmania Medical College, OMC, between 2021 to 2023, were included in the study. Results: Labour was induced, in 47.29%, vaginal delivery in 28 cases, 37.83% and lower segment caesarean section (LSCS) was needed in 46, 62.16% in the study. A total of 90.66% of HELLP have occurred in the third trimester of pregnancy. Eclampsia was associated with HELLP syndrome in 39/100=39%. The remaining 61 cases had preeclampsia associated HELLP syndrome. PRAKI in 31/100=31%, DIC in 19%, PRES in 7/100, PPCM 2%, PPH in 18=24%, maternal mortality in 17/100=17%. Conclusions: Delivery by 37 weeks would have clearly prevented 36% of cases. Delivery by 35 weeks would have prevented 61% of cases of HELLP syndrome.